A clear and effective investment policy is fundamental to ensuring economic development and stability in Uzbekistan. This essay examines the role of investment policy in driving growth and achieving long-term economic security for the country (Zien Journal of Social Sciences and Humanities, 2026)
Uzbekistan pursues a nationally defined economic development path, with economic growth driven by the effective implementation of investment policy. A well-implemented investment policy and a favourable investment climate are essential for sustained GDP growth in the country.